2017
DOI: 10.22610/jebs.v9i4.1831
|View full text |Cite
|
Sign up to set email alerts
|

Government Expenditure and Economic Growth in South Africa: A Vector Error Correction Modelling and Granger Causality Test

Abstract: Previous studies generally find mixed empirical evidence on the relationship between government spending and economic growth. This study re-examine the relationship between government expenditure and economic growth in South Africa for the period of 1990 to 2015 using the Vector Error Correction Model and Granger Causality techniques. The time series data included in the model were gross domestic Product (GDP), government expenditure, national savings, government debt and consumer price index or inflation. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…These findings are in contrast with the Keynesian Macroeconomic Theory probably because the budget structure of the Tanzanian economy comprises hugely by the recurrent expenditure and not development expenditure. This situation is also witnessed in other countries such as South Africa and Nigeria, see (Molefe andChoga, 2017 andOlayungbo andOlayemi, 2018) who investigated the relationship between public expenditure and economic growth, and in accord with the position of the Barro (1990) perspective in his Endogenous Growth Model that, public spending on investments and productive activities should have a positive economic impact, but public spending on consumption is anticipated to inhibit growth because a bigger part of consumer spending is allocated to non-growth aims like redistribution and social welfare.…”
Section: Vector Error Correction Model (Vecm)mentioning
confidence: 84%
See 1 more Smart Citation
“…These findings are in contrast with the Keynesian Macroeconomic Theory probably because the budget structure of the Tanzanian economy comprises hugely by the recurrent expenditure and not development expenditure. This situation is also witnessed in other countries such as South Africa and Nigeria, see (Molefe andChoga, 2017 andOlayungbo andOlayemi, 2018) who investigated the relationship between public expenditure and economic growth, and in accord with the position of the Barro (1990) perspective in his Endogenous Growth Model that, public spending on investments and productive activities should have a positive economic impact, but public spending on consumption is anticipated to inhibit growth because a bigger part of consumer spending is allocated to non-growth aims like redistribution and social welfare.…”
Section: Vector Error Correction Model (Vecm)mentioning
confidence: 84%
“…In this instance, it is necessary to analyze the influence of government spending on economic growth, particularly in emerging nations. Molefe (2017) examined the link between government spending and economic development in South Africa from 1990 to 2015 using the Vector Error Correction Model and Granger Causality approaches. The study's findings demonstrated a negative long-run link between government spending and South African economic development.…”
Section: Introductionmentioning
confidence: 99%
“…The restricted vector autoregressive (Molefe & Choga, 2017) are the inverse roots of the AR characteristic polynomial test that show the model is stable. The results of this test would be made with E-views on the AR root graph, which shows the circle with dotted lines; if dots are within the circle, which means the model is stable.…”
Section: Stability Testmentioning
confidence: 99%
“…Such schools of thought are the conventional Keynesian view and the Ricardian deficit neutrality. According to Molefe and Choga (2017), the conventional Keynesian view supported fiscal deficits as one of the indispensable fiscal policies to enhance aggregate demand, since increasing interest rates would fail dismally. According to Keynes (1937), an economy with no government intervention would collapse as it was evident during the 1939 Great Recession.…”
Section: Literature Reviewmentioning
confidence: 99%